Immortalization of a Primary Human Neonatal Kidney Cell Line - Matthai, Hoyt (My University, 1991)
The purpose of this thesis was to immortalize human neonatal kidney (HNK) cells using oncogenes transferred into the cells in plasmid-DNA clones by microinjection and/or transfection. The oncogenes used were, pSV2neoT24 (ras), FpHVT24 (ras), FpGV-1myc, pSVtsA58 (T antigen), and pSVMTneo (T antigen). Cells were treated with one or two of these oncogenes wherein oncogenic complementarity would be expected e.g. T antigen, ras, and max. Dominant selectable marker genes also in these plasmids were the neomycin resistance gene (pSV2neoT24, pSVMTneo, FpGV-1myc), and the hygromycin resistance gene (FpHVT24). Temperature sensitivity was used for rapid identification of immortalized colonies that continued to propagate beyond normal cell crises and death when pSVtsA58 DNA was used as the oncogene. No resistant/immortal colonies were isolated. To verify the transforming/ immortalizing nature of the oncogenes, a control line of NIH-3T3 was transfected with each of these plasmids. Resistant colonies or foci of immortalized cells were obtained confirming the oncogenic and transforming activity of the DNA clones in the more sensitive NIH-3T3 cell line. In contrast the HNK cells used in this experiment were not transformed after transfection or direct microinjection of the oncogenes ras, law, and large T individually or in combination.